Enzyme-linked immunosorbent assay for determination of antibodies to the envelope glycoprotein of rabies virus. - Grassi, M (1989)
The envelope glycoprotein G of rabies virus induces neutralizing antibodies, which are important in protection against rabies. This protein was solubilized from purified virus and isolated by differential and sucrose density gradient centrifugation followed by high-performance liquid chromatography. Conditions for solubilization and purification of G were optimized by using immunoblotting and enzyme-linked immunosorbent assay techniques. The reaction with conventional antisera and monoclonal antibodies indicated that purified G protein was essentially devoid of internal viral proteins. Microdilution plates were coated with purified G protein, and sera from humans vaccinated against rabies were tested for the presence of antibodies. Results were compared with those of the rapid fluorescent focus inhibition assay, which is the standard neutralization assay for antibodies to rabies virus. The results of this comparison indicate that the enzyme-linked immunosorbent assay for G is a reliable and simple alternative to the neutralization test.